(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background Patient safety is critical component of health care quality. We aimed to assess the awareness of primary healthcare staff members about patient safety culture and explore the areas of deficiency and opportunities for improvement concerning this issue. Methods: This descriptive cross sectional study surveyed 369 staff members in four primary healthcare centers in Kuwait using self-administered “Hospital Survey on Patient Safety Culture” adopted questionnaire. The total number of respondents was 276 participants (response rate = 74.79%). Results: Five safety dimensions with lowest positivity (less than 50%) were identified and these are; the non – punitive response to errors, frequency of event reporting, staffing, communication openness, center handoffs and transitions with the following percentages of positivity 24%, 32%, 41%, 45% and 47% respectively. The dimensions of highest positivity were teamwork within the center’s units (82%) and organizational learning (75%). Conclusion: Patient safety culture in primary healthcare settings in Kuwait is not as strong as improvements for the provision of safe health care. Well-designed patient safety initiatives are needed to be integrated with organizational policies, particularly the pressing need to address the bioethical component of medical errors and their disclosure, communication openness and emotional issues related to them and investing the bright areas of skillful organizational learning and strong team working attitudes.